Enhancing Students’ Participation in English Language Classes Using The ‘Think Pair Share’ Cooperative Learning Model - Nafisah, Shofia Lina; Suwartono, Tono; Noviyanti, Eka; Rahmi, Ade Chusna Silvia (Universitas Pahlawan Tuanku Tambusai, 2024)
This study developed from the need to address concerns with student involvement in the classroom in light of changing educational conceptions. Traditional teaching methods usually result in passive learning experiences for pupils, which can inhibit engagement and comprehension. Recognizing this problem, the goal of this study is to investigate the effectiveness of the ‘Think Pair Share’ cooperative learning approach as a novel strategy for improving student involvement and active participation. This is an action research project that employs questionnaires and observations as the data collection techniques. The research went through three action implementation cycles, each with four stages: planning, implementing, observing, and reflecting. The results obtained in the first cycle showed observation and questionnaire average scores of 66.7 (in a 100 scale) and 52, respectively, which then rose in the second cycle to 72.2 and 88.8. Nevertheless, it did not meet the success criterion of 75. It was only in the third cycle that the minimum intended level was reached, with 86 and 94.5, respectively. Therefore, it is reasonable to conclude that using the Think Pair Share cooperative teaching model can enhance student participation level. Based on the findings of this study, teachers should consider implementing cooperative teaching models to their classrooms.